2021
DOI: 10.3390/ijms221910630
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Long Non-Coding RNA and microRNA Networks in Hepatocellular Carcinoma and Its Tumor Microenvironment

Abstract: Hepatocellular carcinoma (HCC) is a common liver malignancy with high morbidity and poor prognosis. Long non-coding RNAs (lncRNAs) are involved in crucial biological processes of tumorigenesis and progression, and play four major regulatory roles, namely signal, decoy, guide, and scaffold, to regulate gene expression. Through these processes, lncRNAs can target microRNAs (miRNAs) to form lncRNA and miRNA networks, which regulate cancer cell proliferation, metastasis, drug resistance, and the tumor microenviron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 156 publications
0
17
0
Order By: Relevance
“…LncRNAs can sponge miRNAs, which affects the expression of miRNA-targeted genes (69). A growing body of evidence shows that lncRNAs acting as ceRNAs play a significant role in regulating tumor cell proliferation, migration, invasion, apoptosis, immune evasion and drug treatment response (70)(71)(72)(73). For instance, lncRNA LNC00667 plays an oncogenic role by binding to miR-130a-3p, thereby attenuating the inhibition of AR expression and promoting the HCC cell malignant phenotype (71).…”
Section: Sponging Mirnamentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNAs can sponge miRNAs, which affects the expression of miRNA-targeted genes (69). A growing body of evidence shows that lncRNAs acting as ceRNAs play a significant role in regulating tumor cell proliferation, migration, invasion, apoptosis, immune evasion and drug treatment response (70)(71)(72)(73). For instance, lncRNA LNC00667 plays an oncogenic role by binding to miR-130a-3p, thereby attenuating the inhibition of AR expression and promoting the HCC cell malignant phenotype (71).…”
Section: Sponging Mirnamentioning
confidence: 99%
“…A growing body of evidence shows that lncRNAs acting as ceRNAs play a significant role in regulating tumor cell proliferation, migration, invasion, apoptosis, immune evasion and drug treatment response (70)(71)(72)(73). For instance, lncRNA LNC00667 plays an oncogenic role by binding to miR-130a-3p, thereby attenuating the inhibition of AR expression and promoting the HCC cell malignant phenotype (71). LncRNA PICSAR is upregulated in tissues, and gain-and loss-of-function experiments indicated that lncRNA PICSAR enhances cell proliferation and cell cycle progression, inhibits apoptosis by sponging miR-194-5p and subsequently upregulates eukaryotic initiation factor 6 (EIF6) expression in HCC (74).…”
Section: Sponging Mirnamentioning
confidence: 99%
“…It has been suggested that microRNAs (miRNAs) and long noncoding RNAs (lncRNAs) are critical regulators associated with various tumors, in which they are negatively regulated [ 45 ]. Dysregulation of miRNAs and lncRNAs could lead to tumorigenesis in HCC.…”
Section: The Role Of Wnt/β-catenin Signaling Pathway In Hccmentioning
confidence: 99%
“…Dysregulation of miRNAs and lncRNAs could lead to tumorigenesis in HCC. LncRNA-miRNA binding yields a complete endogenous RNA (ceRNA) that can avoid messenger RNA (mRNA) recognition and further silencing effects, known as the “sponge effect” [ 45 ]. Mounting evidence suggests that miRNA sponges are involved in Wnt/β-catenin signaling and are associated with HCC progression ( Table 1 ).…”
Section: The Role Of Wnt/β-catenin Signaling Pathway In Hccmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are approximately 17-24nucleotides-long RNA molecules that are not translated into proteins [16]. miRNAs directly bind to the 3′-untranslated region of their target genes through complementary base pairing and exert a negative regulatory effect on target gene expression, resulting in mRNA degradation and/or translation inhibition [17,18] MiRNAs are important gene expression regulators that contribute to the tumorigenesis and progression of HCC by influencing the malignant phenotype of tumors [19,20]. Recent evidence has revealed a crosslink between miRNAs and lncRNAs, known as the competing endogenous RNA (ceRNA) theory [21][22][23].…”
Section: Introductionmentioning
confidence: 99%